Exploration of Phytochemical, Antioxidant and Anticancer Potential of Syzygium cumini Seeds (Journal of Medical & Health Sciences Review, 2025)
The phytochemical analysis, antioxidant capacity, and anticancer potential of an extract made from Syzygium cumini seeds through green extraction technique are all examined in this work. The existence of bioactive substances with a variety of medicinal uses, including as flavonoids, saponins, steroids, tannins, and alkaloids, was verified by phytochemical screening. According to the DPPH test, which was used to evaluate the antioxidant activity, the extract demonstrated high free radical scavenging activity with an IC50 value of 25.8 µg/ml, in contrast to ascorbic acid's 8.5 µg/ml. Hep3B liver cancer cell lines were used to evaluate the anticancer potential over 24, 48, and 72-hour treatments; the results demonstrated a dose- and time-dependent decrease of cell viability. The extract's IC50 values, which showed increased potency over time, were 77.4 µg/ml, 73.05 µg/ml, and 71 µg/ml, respectively. These results imply that the extract from Syzygium cumini seeds have strong anticancer and antioxidant qualities, which may be related to its diverse phytochemical composition. In addition to recommending more research to identify active chemicals, clarify molecular processes, and evaluate clinical application for cancer therapy, the study validates Syzygium cumini traditional medicinal usefulness.